Kualifikasi Pemimpin Gereja Berdasarkan 1 Timotius 3:1-7 dan Relevansinya Bagi Hamba Tuhan Masa Kini - Laia, Masi Rina (Pusat Riset dan Inovasi Nasional, 2025)
One of the challenges often faced by church leaders is the inability to set a consistent example, which results in the dependence of the ministry and the declining trust of the congregation. This is caused by the imbalance between spirituality and integrity, the influence of lust, and weak spiritual discipline. This study aims to exmine the qualifications of church leaders in general, and analyze their relevance for God’s service in the present era. The method used is qualitative with a hermeneutic descriptive-analytical approach, accompanied by a literature study sourced from theological literature, tafsir, and related articles. The result show that church leaders must have moral integrity, self-control, loyalty, wisdom, skill, teaching, and a good reputation. These criteria become the foundation of spiritual leadership eligiblity. The conclusion of this study emphasizes that servants of God must live in love, live simply, be authoritative, humble and able to adjust to the dynamics of today’s ministry.